Central Bank communication and monetary policy: a survey of theory and evidence - Alan S. Blinder; Michael Ehrmann; Jakob de Haan; Marcel Fratzscher; David-Jan Jansen (European Central Bank (ECB), 2008)
Over the last two decades, communication has become an increasingly important aspect of monetary policy. These real-world developments have spawned a huge new scholarly literature on central bank communication —mostly empirical, and almost all of it written in this decade. We survey this evergrowing literature. The evidence suggests that communication can be an important and powerful part of the central bank's toolkit since it has the ability to move financial markets, to enhance the predictability of monetary policy decisions, and potentially to help achieve central banks' macroeconomic objectives. However, the large variation in communication strategies across central banks suggests that a consensus has yet to emerge on what constitutes an optimal communication strategy.
Keywords: E52; E58; 330; Central Bank; communication; monetary policy; Geldpolitik; Zentralbank; Kommunikation; Ankündigungseffekt; Industrieländer